Solution architecture foundations - Lovatt, Mark (BCS, The Chartered Institute for IT, 2021)
This authoritative, practical introduction to solution architecture is suitable for new entrants to the field but also of benefit to experienced professionals wishing to consolidate their knowledge and skills. Tools and techniques are presented in context, taking a problem or idea through logical steps to design a holistic, evidence-based solution.